2010
DOI: 10.1111/j.1365-2672.2010.04863.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro lung delivery of bacteriophages KS4-M and ΦKZ using dry powder inhalers for treatment of Burkholderia cepacia complex and Pseudomonas aeruginosa infections in cystic fibrosis

Abstract: Development of lactoferrin-based bacteriophage aerosol powders solidifies the ground for future research on developing novel formulations as an alternative to inhaled antibiotic therapy in patients with cystic fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
81
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(85 citation statements)
references
References 58 publications
1
81
0
Order By: Relevance
“…In contrast, phage particle aerosols generated by a nebulizer and delivered via a NOID constitute a better method for alveolar phage deposition (32). Several recent studies suggested that aerosol phage therapy is not only possible but that it can be an effective method for delivering phages directly to the site of a pulmonary bacterial infection (32,33,48). In this study, immunocompromised and BCC-infected mice receiving aerosolized phage treatments exhibited significant decreases in bacterial loads within the lungs.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…In contrast, phage particle aerosols generated by a nebulizer and delivered via a NOID constitute a better method for alveolar phage deposition (32). Several recent studies suggested that aerosol phage therapy is not only possible but that it can be an effective method for delivering phages directly to the site of a pulmonary bacterial infection (32,33,48). In this study, immunocompromised and BCC-infected mice receiving aerosolized phage treatments exhibited significant decreases in bacterial loads within the lungs.…”
Section: Discussionmentioning
confidence: 71%
“…Although these studies have investigated phage therapy in different mouse infection models, they have done so using intranasal instillation as the delivery method (22)(23)(24)(25), which is inefficient and produces significant phage loss through ingestion. We have previously demonstrated that phages can be successfully aerosolized without damage (32,33), and utilizing this knowledge, we demonstrate here that aerosol phage therapy in mice is effective with phages delivered as a nebulized aerosol. Direct aerosolization of a therapeutic agent is the ideal method of delivery when treating a patient with a respiratory infection, and this method is an established mode of chemical drug delivery (34).…”
mentioning
confidence: 95%
“…1) and can be assigned to the order Caudovirales and family Myoviridae based on this morphology. Phage KS4-M has been used successfully in both nebulization and lyophilization studies 22,19 and is easy to obtain in high titers.…”
Section: Bacteriophagesmentioning
confidence: 99%
“…21 Freezedrying with subsequent micronization has been successfully applied to bacteriophages for respiratory delivery. 22 An acceptable titer loss was found on processing and the in vitro performance of the resulting powder demonstrated efficient delivery by a dry powder inhaler (DPI).…”
Section: Introductionmentioning
confidence: 99%
“…These phages are distributed widely geographically and are of interest because those infective for pathogens have been used for phage therapy (4) and/or have potential for further biocontrol applications (5)(6)(7)(8). These phages are also a curiosity, as they are remarkably complex, both at the genome and structural levels, with large virions comprised of a Tϭ27 capsid or head (9) and contractile tail that ends in an elaborate baseplate (10,11).…”
mentioning
confidence: 99%